Empowering women through microcredit in bangladesh: An empirical study - Dalia Debnath; Md. Sadique Rahman; Debasish Chandra Acharjee; Waqas Umar Latif; Linping Wang (International Journal of Financial Studies, 2019)
The present study was carried out to identify the determinants of microcredit accessibility by rural women households and its impact on rural women empowerment in Bangladesh. A face-to-face survey was conducted during 2018, interviewing 300 women households in two locations in Bangladesh. Descriptive statistics and econometric modeling were used to achieve the objectives. The results of the study showed that the higher annual income inversely related with the accessibility to the microcredit program, whereas family size (P < 0.05) was positive and significantly influenced the accessibility to the microcredit program. The empirical results indicate that borrowers of microcredit have greater control over their own savings. The regression outcome also exposes that microcredit has a positive and significant impact on enhancing participation in household decision making process and women's legal awareness. The study suggested that microcredit providers in Bangladesh should be encouraged to review their program planning and redesign loan products by putting more emphasis on higher income group women.
Keywords: 330; microcredit; accessibility; women’ s empowerment; logit regression; Bangladesh